2013
DOI: 10.1116/1.4825202
|View full text |Cite
|
Sign up to set email alerts
|

Ashing of photoresists using dielectric barrier discharge cryoplasmas

Abstract: Plasma ashing of photoresists is a critical step in advanced microelectronics manufacturing as it often leads to extensive damage in porous organosilicate low-j dielectrics and hinders the use of highly porous films in interconnects. To reduce plasma damage, the authors investigated the feasibility of ashing a 248-nm photoresist with cryoplasma. The authors ashed photoresist-coated silicon wafers with dielectric barrier discharge microplasma generated at temperatures of 170-291 K, a pressure of 100 Torr, appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Even if the preliminary results were promising, there has been very little investigations of such processes in the literature. [21,22] …”
Section: Plasma Etching With Barrier Passivation Layersmentioning
confidence: 98%
“…Even if the preliminary results were promising, there has been very little investigations of such processes in the literature. [21,22] …”
Section: Plasma Etching With Barrier Passivation Layersmentioning
confidence: 98%
“…A more detailed analysis of the effect of cryoplasma ashing on photoresists revealed that depending on the temperature and gas composition, different types of molecular groups are removed or modified [48]. So far, there have been no specific applications, but we believe the inherent ability of cryoplasmas to actively control the plasma chemistry and gas temperature with modest local heating can enable their use in emerging fields of plasma science and technology, namely plasma medicine and biotechnology.…”
Section: Applicationsmentioning
confidence: 99%
“…These studies reported that certain reaction rates strongly depend on T g . For example, the reaction rate constant of the metastable He (He m ) conversion reaction (R6 in table 1) strongly depends on the gas temperature [12] and was too low to be measured below 65 K, due to a small hump in the potential energy for the combination of He atoms in the 2 3 S and 1 1 S states [21], which results in the existence of the activation energy (∼0.067 eV) [11]. Also, the slow decay of plasma afterglow due to long ambipolar diffusion lengths [22] and a long relaxation time for the rotational distribution of He 2 molecules [23,24] have been reported.…”
Section: -Dimensional (Global) Reaction Modelmentioning
confidence: 99%
“…for the treatment of highly heat sensitive materials such as nano-porous structures and frozen materials. For example, it has been reported that the effective reduction of T g reduces damage in nano-porous low-k materials during ashing [2,3].…”
Section: Introductionmentioning
confidence: 99%